Stimulasi Perkembangan Fisik Motorik Melalui Permainan Tradisional Egrang Batok - Jumawan, Jumawan; Wulandari, Rifa Suci; Lestari, Endang (MENTARI: Jurnal Pendidikan Anak Usia Dini, 2024)
The physical motor development aspect is a developmental phase in the elements of maturity in body movement that is closely related to the development of the motor center in the brain. With a gradual increase in age, movement increases from undeveloped and unskilled to very well developed. The aim of this research is to find out and describe the application of the traditional egrang batok game as a medium for stimulating the physical motor development of group B children at the Pembina Ponorogo State Kindergarten. This research design uses descriptive research. Data collection techniques use observation, interviews, and official documentation. The data analysis technique uses analysis techniques according to Miles and Huberman, with stages of data reduction, data display, and conclusion drawing. The results of the research show that the application of the traditional game of egrang batok as a medium for stimulating the physical motor development of group B children at the Pembina Ponorogo State Kindergarten has developed as expected. When the traditional game of stilt batok is played regularly, it is proven to really help children’s physical motor development and helps stimulate aspects of concentration, eye, hand to foot coordination, as well as agility, speed and accuracy in playing. Suggestions for readers who will carry out qualitative field research on aspects of children’s physical motor development: do it carefully and focus so that the research results are more valid.